Preparation and characterization of copper, iron, and nickel doped titanium dioxide photocatalysts for decolorization of methylene blue - Qaderi, Jawed; Che Rozid Mamat,; Aishah Abdul Jalil, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The visible-light response is a necessary condition for titanium dioxide (TiO2 ) photocatalyst to function as a visible light active photocatalyst. This condition can be solved by investigation of the bandgaps and the optimization of doping levels of multivalency metal-doped TiO2 . In this study, pure and Cu, Fe, and Ni-doped TiO2 photocatalysts were prepared by the sol‐gel method. The photocatalysts were characterized using XRD, FTIR, FESEM, EDX, N2 physisorption, and UV‐Vis spectrophotometry techniques. The XRD patterns of all pure TiO2 and Cu/TiO2 , Fe/TiO2 , and Ni/TiO2 samples showed the dominant structure of the anatase TiO2 phase. The presence of functional groups at the interface of TiO2 particles was showed by FTIR. The FESEM analysis showed that the particle size of the prepared samples was uniform with spherical morphology. EDX results showed that TiO2 has successfully incorporated Cu, Fe, and Ni metals onto its surface. The BET analysis showed that the specific surface area of the doped samples increased with the amount of doping. The optical properties of all samples were carried out using UV-DRS measurements and their obtained bandgap energies were in the range of 3.22 - 3.42 eV. The pure TiO2 displayed more than 98% and 97% decolorization rates for MB solution at the end of irradiation time of 5 h under UV and visible light, respectively. Among the doped samples, 3 mol% Ni/TiO2 and Cu/TiO2 demonstrated the highest photocatalytic activity (97.65%) under UV light and 6 mol% Ni/TiO2 under visible light for MB (96.86%) decolorization.